Ibadah Amaliyah sebagai Bentuk Kearifan Lokal Kepesantrenan di Pondok Pesantren Darul Hijrah Puteri Martapura - Ramadhana, Zahra Aulia (FTIK UIN Sultan Aji Muhammad Idris Samarinda, 2025)
Amidst the digital current, where secular values dominate, practical worship as local wisdom is needed to strengthen the resilience of Islamic cultural identity. Thru this research, which focuses on understanding and practicing practical worship in pesantren, it is hoped that practical worship activities will serve as a means of reflection and strengthening the pesantren's identity in the eyes of the wider community, demonstrating that the tradition of practical worship is not merely an activity, but an integral part of a comprehensive Islamic education system. This research aims to analyze the forms of practical worship as a manifestation of local wisdom in pesantren at Pondok Pesantren Darul Hijrah Puteri Martapura. Practical worship at Pondok Pesantren Darul Hijrah Puteri is not only a religious activity, but also an integral part of the pesantren education system. The distinctive feature of practical activities carried out collectively and in a structured manner is a strong identity for this pesantren in preserving Islamic values while also shaping the character of the younger generation.